Disrupting Management Research? Critical Reflections on British Journal of Management COVID‐19 Research and an Agenda for the Future. (16th December 2022) - Brammer, Stephen; Branicki, Layla; Linnenluecke, Martina
Abstract: Research interest in extreme contexts was growing before the COVID‐19 pandemic and has intensified since. The climate crisis, significant geo‐political conflict, political polarization and upheaval, and economic/financial crises that present existential challenges to organizations have all contributed to rising interest in extreme‐context research. COVID‐19 itself has generated an enormous body of research across all sub‐fields of management. However, the substantive, methodological and conceptual implications of this large volume of research remain unclear. In this introduction to the British Journal of Management COVID‐19 Online Virtual Issue, we describe and analyse COVID‐19 research so far published in the British Journal of Management . The Journal was proactive in seeing the profound implications of COVID‐19 for management research and practice, issuing an early call for contributions, and publishing several exploratory commentaries as early as July 2020. In this paper, we situate COVID‐19 research within the broader extreme‐context research, analyse contributions made so far, and build upon an extended taxonomy of extreme contexts to suggest ways for future research to generate further impactful insights.